The eyes have it: an exploration of eye movements in action disorganisation syndrome. - Forde, E; Rusted, J; Mennie, N; Land, M; Humphreys, G (2010)
We examined eye movements in a patient, FK, who has action disorganisation syndrome (ADS), as he performed the everyday task of making a cup of tea. We compared his eye movements with those of a person with Alzheimer's disease and with healthy volunteers. Despite showing very disorganised behaviour many aspects of FK's eye movements were relatively normal. However, unlike normal participants FK made no advance glances to objects that were about to be used, and he made increased numbers of fixations to irrelevant objects during the task. There were also differences in the durations of his eye movements during correct actions and during his perseverative and task-addition responses. We discuss the implications for understanding ADS and the cognitive processes required for correctly performing everyday tasks.